2020
DOI: 10.1111/ejn.14960
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence quantification analysis of dynamic brain networks

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 71 publications
(120 reference statements)
0
20
0
Order By: Relevance
“…The microstate connectivity approach presented here also has potential as an alternative approach for studying dynamic functional connectivity. A typical approach for dynamic functional connectivity in the current literature is the use of a sliding window (de Pasquale et al, 2010; Brookes et al, 2014; O’Neill et al, 2015; de Pasquale et al, 2016; Lopes et al, 2020), which is limited by the arbitrary choice of window size meaning development of novel methods beyond the sliding window are crucial (O’Neill et al, 2018). Our MVPA analysis indicated that windowing via microstate labelling and concatenation of samples within a state (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The microstate connectivity approach presented here also has potential as an alternative approach for studying dynamic functional connectivity. A typical approach for dynamic functional connectivity in the current literature is the use of a sliding window (de Pasquale et al, 2010; Brookes et al, 2014; O’Neill et al, 2015; de Pasquale et al, 2016; Lopes et al, 2020), which is limited by the arbitrary choice of window size meaning development of novel methods beyond the sliding window are crucial (O’Neill et al, 2018). Our MVPA analysis indicated that windowing via microstate labelling and concatenation of samples within a state (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…A second limitation of this approach is that it relies on the assumption of a discrete number of functional connectivity states. While this assumption does not apply in general to sliding-window connectivity studies, common subsequent analyses such as clustering networks (Allen et al, 2014; O’Neill et al, 2015; Mheich et al, 2015; Hassan et al, 2015) or recurrence analysis (Lopes et al, 2020) make similar assumptions, and hence microstate-windowing can be viewed as an alternative to these approaches without the reliance on window length.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a temporal network of PPIs, nodes represent proteins, and interactions between them are represented by time-varying edges. Temporal network theory has been used successfully in areas ranging from social interactions (Miritello et al 2011; Saramäki and Moro 2015; Gelardi et al 2020) to neuroscience (Pedreschi et al 2020; Lopes et al 2021). However, despite calls to use it more in biology (Przytycka et al 2010), it is still underused to study, e.g., PPI networks.…”
Section: Introductionmentioning
confidence: 99%
“…Other methods for EEG/MEG analyses are available to examine to rapid changes in brain-state. One is to apply sliding window analysis to the EEG/MEG time courses [24][25][26][27][28] and subsequently cluster functional networks across windows 21;26;29;30 . This approach has the limitation of the need for an arbitrary a priori selected window size: too short windows lead to results susceptible to noise, while too large windows result in non-stationarity at fast time scales being missed 10 .…”
Section: Introductionmentioning
confidence: 99%